ENT 530 Social Media Portfolio: NZ Crunchies / Muhammad Aliff Ahmad Za'im - Ahmad Za'im, Muhammad Aliff (2021)
For this semester, all of students that take Entrepreneurship subject have to choose one product and sell them. The purpose for this report was to analyze and observe the credibility of the company on what kind of marketing strategy that they choose in order for them to enhance the customer awareness regarding the products that they had sold. One of the most famous tools that company used to attract and gain customers is through social media which is Facebook and make them purchase product. In addition, this report also reported on how frequent the company promoting and advertise their product in the social media especially Facebook. Facebook was chosen because many people nowadays including all range of ages that used Facebook. Each company required to post varieties of strategies to advertise the product. In posting at the Facebook it includes the teasers, hard sells, and also soft sells. This is because social media is a good way for engaging and interacting customer. The more company communicate with the audience, the more chances company have of conversion and this will create two-way communication. As Facebook provides many kinds of advertising, it could help company to reach their potential customer faster than other company could do. This will make the company could achieve their targets to increase their sales. It also can gain interests about the product that they sell towards their customers. Thus, Facebook connection makes company and customers are more probable to upsurge customer retention and customer loyalty.